Pelatihan Pengolahan Motif Totebag Teknik Eco Printing pada Ibu PKK Desa Padelegan - Nikmah, Ainun; Rahmawati, Ika Dian; A'yun, Dya Qurotul; Ningsih, Puji Rahayu (Yayasan Arrahman Nahdlatul Wathan, 2025)
Training on processing tote bag motifs using eco printing techniques in Padelegan Village aims to introduce new environmentally friendly skills while increasing the creativity and economic potential of PKK women. The eco printing technique uses natural materials, such as leaves and flowers, to print motifs on textile media, producing products of high artistic value. This training was carried out by students of the Trunojoyo Madura University Thematic Real Work Lecture (KKNT), which was carried out in two stages: first, socialization and making mordant on tote bags, and second, printing motifs using pounding techniques. The results of the training showed that participants were able to master eco printing techniques and produce tote bags with natural motifs that could be sold, providing new business opportunities for PKK women. Participants' responses showed high enthusiasm and a desire to develop these skills further as a business opportunity. It is hoped that this training will not only improve skills, but can also contribute to family economic empowerment and nature conservation through environmentally friendly products.